'Do not attempt CPR' in the community: the experience of ambulance clinicians. (2nd May 2019) - Moffat, Suzanne; Fritz, Zoë; Slowther, Anne-Marie; Parry, Matthew; Barclay, Stephen
Abstract : Background: Ambulance clinicians must make time-critical decisions concerning treatment and resuscitation. Little is known about the impact of the presence (or absence) of do-not-attempt cardiopulmonary resuscitation (DNACPR) decision forms in the community. Aims: To investigate ambulance clinicians' experiences of DNACPR documentation and views concerning potential future changes. Methods: This multi-methods study used semi-structured face-to-face interviews ( n =10) and an online questionnaire ( n =123) Findings: Ambulance clinicians report that a statistically significant increase in numbers of community DNACPR forms has occurred in recent years. Most state they have not had formal DNACPR education and experience difficulties in making clinical judgments about patients at the end of life, reporting inappropriate CPR attempts and poor communication among stakeholders. Conclusion: Assessment of patients near the end of life with (and especially without) a DNACPR is challenging for ambulance clinicians. Education about resuscitation recommendations needs to be integrated into training and a national approach should be taken to decisions and their documentation.